Il paese dei balocchi: Pinocchio tra Paradiso e Inferno (Altre Modernità, 2012)
"What a wonderful, beautiful, marvelous country! Oh--h--h!!",says Pinocchio at the end of the Chapter XXX of “The Adventures”, after Lamp-Wick explained him the amazing features of the "real country--the best in the world--a wonderful place!": the Land of Toys, also named “blessed place” and portrayed as a sort of heaven on heart for lazy boys.In reality, the approaching road to the Land of Toys, before as a mental process, - a persuasion of himself – and then as real journey, it’s like a fall to hell.The master of ceremonies of this fall to hell is just the fellow Lamp-Wick,in fact in the original version of the book Lamp-Wick is “Lucignolo”, a name reminiscent of Lucifer, the famous fallen angel.Lamp-Wick and Pinocchio work up to the Land of Toy in a wagon conducted by a spineless, shifty driver: “a little, fat man, muchwiderthan he was long, round and shinyas a ball of butter, with a face beaminglike an apple, a little mouth that always smiled, and a voice small and wheedling like that of a catbegging for food”.This “little, fat man” is a sort of Charon, and the wagon: “wasdrawn by twelve pair of donkeys, all of the same size, but all of different color. Some weregray, otherswhite, and still others a mixture of brown and black. Here and there were a few with large yellow and blue stripes.”.These queerd on keys, recurring frequently in the fairytale and they are full of double meaning: in half way point between the numinoso Christ’s whitehorse and the demonic Cambridge Bestiary.Pinocchio and Lamp-Wick glorify the life in the Land of Toys: they feel free and happy like in heaven, but the hard truth is very different: this land looks like the Hell, everywhere is noise, disorder, insecurity.During the development of the story, it’s possibile to detect different elements of the Pinocchio’s rise and fall between Heaven and Hell. For example the double nature of the Fairy: during the tale she can be the ghost of the little girl (de facto an angel) or she can be a goat (a devil’s mark).Talking about rise and fall, the end of the story is paradigmatic: Pinocchio will get a real boy. Acquiring the human nature, he will be able to find the Heaven on earth, after a long series of ups and downs, starting with a “badhell night”.
Keywords: Pinocchio; Infanzia; Inferno; Paradiso; Metamorfosi; Eden